Fiber-Type-Specific Transcription of the Troponin I Slow Gene Is Regulated by Multiple Elements - Calvo, Soledad (American Society for Microbiology, 1999)
The regulatory elements that restrict transcription of genes encoding contractile proteins specifically to either slow- or fast-twitch skeletal muscles are unknown. As an initial step towards understanding the mechanisms that generate muscle diversity during development, we have identified a 128-bp troponin I slow upstream element (SURE) and a 144-bp troponin I fast intronic element (FIRE) that confer fiber type specificity in transgenic mice (M. Nakayama et al., Mol. Cell. Biol. 16:2408–2417, 1996). SURE and FIRE have maintained the spatial organization of four conserved motifs (3′ to 5′): an E box, an AT-rich site (A/T2) that binds MEF-2, a CACC site, and a novel CAGG motif. Troponin I slow (TnIs) constructs harboring mutations in these motifs were analyzed in transiently and stably transfected Sol8 myocytes and in transgenic mice to assess their function. Mutations of the E-box, A/T2, and CAGG motifs completely abolish transcription from the TnI SURE. In contrast, mutation of the CACC motif had no significant effect in transfected myocytes or on the slow-specific transcription of the TnI SURE in transgenic mice. To assess the role of E boxes in fiber type specificity, a chimeric enhancer was constructed in which the E box of SURE was replaced with the E box from FIRE. This TnI E box chimera, which lacks the SURE NFAT site, confers essentially the same levels of transcription in transgenic mice as those conferred by wild-type SURE and is specifically expressed in slow-twitch muscles, indicating that the E box on its own cannot determine the fiber-type-specific expression of the TnI promoter. The importance of the 5′ half of SURE, which bears little homology to the TnI FIRE, in muscle-specific expression was analyzed by deletion and linker scanning analyses. Removal of the 5′ half of SURE (−846 to −811) results in the loss of expression in stably transfected but not in transiently expressing myocytes. Linker scanning mutations identified sequences in this region that are necessary for the function of SURE when integrated into chromatin. One of these sites (GTTAATCCG), which is highly homologous to a bicoid consensus site, binds to nuclear proteins from several mesodermal cells. These results show that multiple elements are involved in the muscle-specific activity of the TnIs promoter and that interactions between upstream and downstream regions of SURE are important for transcription in the context of native chromatin.